Doctor Ernesto Odriozola - Valega, Juan Francisco (1921)
We add a simple and exciting youth early grave note from the teacher. In this time of national mourning for the medicine, it would be pretty tough justifying the excitement we have experienced, to fail to express the magnitude of a sentence, that each and every one of us reaches and moves.